Genetically modulated educational attainment and coronary disease risk. (6th June 2019) - Zeng, Lingyao; Ntalla, Ioanna; Kessler, Thorsten; Kastrati, Adnan; Erdmann, Jeanette; ,; Danesh, John; Watkins, Hugh; Samani, Nilesh J; Deloukas, Panos; Schunkert, Heribert
Abstract: Aims: Genetic disposition and lifestyle factors are understood as independent components underlying the risk of multiple diseases. In this study, we aim to investigate the interplay between genetics, educational attainment—an important denominator of lifestyle—and coronary artery disease (CAD) risk. Methods and results: Based on the effect sizes of 74 genetic variants associated with educational attainment, we calculated a 'genetic education score' in 13 080 cases and 14 471 controls and observed an inverse correlation between the score and risk of CAD [ P = 1.52 × 10 −8 ; odds ratio (OR) 0.79, 95% confidence interval (CI) 0.73–0.85 for the higher compared with the lowest score quintile]. We replicated in 146 514 individuals from UK Biobank ( P = 1.85 × 10 −6 ) and also found strong associations between the 'genetic education score' with 'modifiable' risk factors including smoking ( P = 5.36 × 10 −23 ), body mass index (BMI) ( P = 1.66 × 10 −30 ), and hypertension ( P = 3.86 × 10 −8 ). Interestingly, these associations were only modestly attenuated by adjustment for years spent in school. In contrast, a model adjusting for BMI and smoking abolished the association signal between the 'genetic education score' and CAD risk suggesting an intermediary role of these two risk factors. Mendelian randomization analyses performed with summary statistics from large genome-wide meta-analyses and sensitivity analysis using 1271 variants affecting educational attainment (OR 0.68 for the higher compared with the lowest score quintile; 95% CI 0.63–0.74; P = 3.99 × 10 −21 ) further strengthened these findings. Conclusion: Genetic variants known to affect educational attainment may have implications for a health-conscious lifestyle later in life and subsequently affect the risk of CAD.